Atmospheric pollution due to improper industrial siting : A meteorological approach for abatement (MAUSAM, 1978)
A simple method utilising the conventional meteorological data to advise on (a) optimum stack height of any proposed industry to limit the pollutant concentrations within their lethal values and (b) optimum emission With the existing stack height of an operating industry to control the concentrations within the standard limits is presented. In-developing this methodology a comparison was also made of the stability classification of Pasquill-Turner, critical values of Riohardson 's number and limits of standard deviation of wind directions. Of these the best classification was found to be by using wind direction traces. Plume rise by Briggs, Tennessee Valley Authority, Holland, Whaley, Morton, CONCA WE and Lucasmethods were compared and the study points out that Lucas formula could be employed wIth lI1inimum data without losing much accuracy as often claimed by Sophisticated formulae. Coefficients for vertical variation of Wind were derived from continuous records over a tower at two levels. Temperature variation in the vertical under daylight conditions is assumed to be dry adiabatic. During night time inversions a mathematical model derived from screen temperature data is used. Maximum concentration and its distance were obtained for 03 and 12 GMT for every month from climatological data. Where there concentrations were found to be lower than United States Environmental Protection Agency (EPA) Becondary8'tandard the stack heights are considered to be safe provided the background pollution is negligible; otherwise the optimum stack heights were determined. Alternatively with the limit of EPA  standard, existing stack height and meteorological parameters the optimum emission rate is determined. These industries in the proposal stage can modify the stack design but for industries in production stage emission rate to be limited.